Embedded Critical Software Testing for Aerospace Applications based on PUS - Pontes, Rodrigo P.; Martins, Eliane; Ambrósio, Ana M.; Villani, Emília (Anais do Workshop de Testes e Tolerância a Falhas (WTF); 2010: Anais do XI Workshop de Testes e Tolerância a FalhasDO - 10.5753/wtf.2010.23100, 2010)
This paper discusses the practical experience of verifying an On-Board Data Handling (OBDH) software to be used in a future satellite application at INPE using the CoFI testing methodology. This technique is proper for aerospace applications and is based on modeling the system under test as finite state machines. The test cases are automatically generated from the developed models. The OBDH software considered in this paper follows the PUS standard from European Cooperation for Space Standardization, which is being adopted in Brazil. Among the important issues analyzed by this practical experience are the errors found, the time required for the modeling activity, the time required for testing, the reusability of the test cases, among others.